Morbidity pattern of commercial long distance bus drivers in Benin City, Edo State, Nigeria - Chinedu, Okafor Kingsley; O., Omuemu Vivian; A. , Okoh-Oboh Gregory; Hilda, Okogie Obehi; O., Idoko Lucy (Jour Med Resh and Health Sci, 2023)
Introduction: Long distance commercial driving as an occupation exposes drivers to various disease conditions. Commercial driving is a hazardous occupation as long hours are spent driving on risky highways. This study seeks to determine the morbidity pattern among commercial long distance drivers, and factors affecting it. Materials and methods: A descriptive cross sectional study design was used, and data was collected from 315 commercial long distance drivers from January to October, 2013. Respondents were recruited using systematic random sampling technique. Study instruments included structured interviewer administered questionnaires. Results: The results showed that all respondents had a normal neurological and abdominal examinations, 9.5% had abnormal fasting blood glucose levels. A third (33.3%) were hypertensive, 29.9% were pre-hypertensive, nearly half (48.3%) were overweight, 12.7% obese, 39.0% had normal BMI obese, majority 87.6% had an abnormal waist-hip ratio. Twenty six (8.3%) said they face stress always and 40.6% stated that they face stress sometimes. Most (80.3%) revealed that their cause of stress were work related, 4.1% were due to home problems and 15.6% both work and homes issues. On diagnosed morbidity pattern and perceived health problems, 31.4% of drivers were currently being treated by a doctor at the time of the study due to illness, 12.4% were diagnosed of hypertension and heart disease, 11.7% diagnosed of peptic ulcer, 9.2% had joint pains (shoulder, elbow, wrist, hip, knee, ankle joints) , 9.2% had URTI, 5.4% impaired vision, 5.1% had diabetes, 5.1% had back pain, 1.6% had a blackout and fainting spells, 0.6% hypoglycaemic event, while 1 (0.3%) had suffered a stroke On self reported morbidity, about three quarters of the drivers (74.6%) complained of back pain, others in the previous six months were Malaria (66.0%), headache (63.8%), Fever from other causes (52.7%). fatigue (51.7%) , cough (43.5%) , cold and catarrh (42.9%). Other health problems mentioned were neck pain (41.9%), drunk on alcohol (24.8%), visual problems (26.0%), Hypertension (9.5%), ear ache (8.9%) , pneumonia (7.0%), haemorrhoids (5.7%) , 15 (4.8%) diabetes, penile discharge (9.2%), No respondent reported having seizures, kidney disease, hearing problem and psychiatric illness. Conclusion:.Common morbidities affecting commercial drivers as diagnosed by a doctor include: hypertension, heart disease, peptic ulcer, joint pains, upper respiratory tract infection (URTI), back pain, diabetes, and impaired vision. Health problems based on their perception were back pain, malaria, headache, fever from other causes, fatigue, cough, cold and catarrh, neck pain, penile discharge, ear ache and visual problems.